Heutagogy in Indonesian Higher Education: Cultural Challenges and Opportunities in Online EFL Learning - Friska, Yuliana; Purnama, Syahfitri; Miranti, Ira (Journal of English Language and Education, 2025)
This study highlights the importance of the application of heutagogy in online EFL learning in higher education, which is still rarely studied in the Indonesian context. There is a gap between heutagogy theories that emphasize learning autonomy and EFL teaching and learning that tend to be lecturer-centric. This study aims to analyze cultural challenges and opportunities in the application of heutagogy from the perspective of lecturers and students. Using a qualitative approach, data were collected through semi-structured interviews with participants from Universitas Pamulang and analyzed using thematic analysis. The results of the study show that there are cultural barriers such as lecturer-centered learning, a hierarchical educational structure, cultural views related to respect and obedience to lecturers, and language proficiency barriers. However, opportunities were also found in the form of increased autonomy, engagement, communication, collaboration, critical thinking skills, and fostering a lifelong learning mindset. This study concludes that heutagogy has the potential to enrich EFL pedagogy in Indonesia with the need for contextual implementation strategies and sustainable lecturer capacity development.